Non-metal-templated approaches to bis(borane) derivatives of macrocyclic dibridgehead diphosphines via alkene metathesis - Fiedler, Tobias; Barbasiewicz, Michał; Stollenz, Michael; Gladysz, John A. (Beilstein Journal of Organic Chemistry, 2018)
Two routes to the title compounds are evaluated. First, a ca. 0.01 M CH2Cl2 solution of H3B·P((CH2)6CH=CH2)3 (1·BH3) is treated with 5 mol % of Grubbs' first generation catalyst (0 °C to reflux), followed by H2 (5 bar) and Wilkinson's catalyst (55 °C). Column chromatography affords H3B·P(n-C8H17)3 (1%), H3B·P((CH2)13CH2)(n-C8H17) (8%; see text for tie bars that indicate additional phosphorus–carbon linkages, which are coded in the abstract with italics), H3B·P((CH2)13CH2)((CH2)14)P((CH2)13CH2)·BH3 (6·2BH3, 10%), in,out-H3B·P((CH2)14)3P·BH3 (in,out-2·2BH3, 4%) and the stereoisomer (in,in/out,out)-2·2BH3 (2%). Four of these structures are verified by independent syntheses. Second, 1,14-tetradecanedioic acid is converted (reduction, bromination, Arbuzov reaction, LiAlH4) to H2P((CH2)14)PH2 (10; 76% overall yield). The reaction with H3B·SMe2 gives 10·2BH3, which is treated with n-BuLi (4.4 equiv) and Br(CH2)6CH=CH2 (4.0 equiv) to afford the tetraalkenyl precursor (H2C=CH(CH2)6)2(H3B)P((CH2)14)P(BH3)((CH2)6CH=CH2)2 (11·2BH3; 18%). Alternative approaches to 11·2BH3 (e.g., via 11) were unsuccessful. An analogous metathesis/hydrogenation/chromatography sequence with 11·2BH3 (0.0010 M in CH2Cl2) gives 6·2BH3 (5%), in,out-2·2BH3 (6%), and (in,in/out,out)-2·2BH3 (7%). Despite the doubled yield of 2·2BH3, the longer synthesis of 11·2BH3 vs 1·BH3 renders the two routes a toss-up; neither compares favorably with precious metal templated syntheses.
Keywords: alkene metathesis; crystal structures; homeomorphic isomerization; hydrogenation; in/out isomers; metathesis; phosphine boranes